Traditional knowledge on the use of local food crops by Togutil Ethnic in Halmahera Island, Indonesia - M. NASIR TAMALENE (Asian Journal of Agriculture, 2017)
Abstract. Tamalene MN. 2017. Traditional knowledge on the use of local food crops by Togutil Ethnic in Halmahera Island, Indonesia. Asian J Agric 1: 66-72. Food crop is an important component in the life system of the Togutil ethnic group in Halmahera Island. The main characteristic of the group is their nomadic life, despite the existence of some sedentary groups. Generally, the group consumes wild food plants growing in their natural ecosystem. This paper presents a selected result of food crop studies conducted in Halmahera Island, Indonesia. The botanical supply of food crops of the Togutil has high usefulness in their social and cultural activities. Data was collected through in-depth interview method with key informants chosen based on purposive sampling. Plant species were identified in the Laboratory of Herbarium Botany Bogoriense of the Biological Research Center of Indonesian Institute of Science (LIPI). 48 species of 23 families of food crops are used by the Togutil tribe of Halmahera Island, Indonesia. The food crops identified were wild plants with 45.83% growing in bushes habitat and primary forest, with 56.25% being cultivated crops planted in the garden and yard. Other uses of the food crops were identified as being medicinal plants (64.28%), house building (29.17%), and handicrafts and adhesive for animal (4.17%). In the cultural aspect, food crops were used for hunting rituals, medium of exchange (barter), welcoming guest rituals and traditional rituals. The value of Cultural Food Significance Index (CFSI) in the very high significance category was 64.58%, high significance was 27.08%, and low significance and very low significance are 4.16%.